2014
DOI: 10.1186/s12913-014-0568-3
|View full text |Cite
|
Sign up to set email alerts
|

Notifiable disease reporting among public sector physicians in Nigeria: a cross-sectional survey to evaluate possible barriers and identify best sources of information

Abstract: BackgroundSince 2001, Nigeria has collected information on epidemic-prone and other diseases of public health importance through the Integrated Disease Surveillance and Response system (IDSR). Currently 23 diseases are designated as “notifiable” through IDSR, including human infection with avian influenza (AI). Following an outbreak of highly pathogenic avian influenza A(H5N1) in Nigerian poultry populations in 2006 and one laboratory confirmed human infection in 2007, a study was carried out to describe knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 8 publications
3
23
0
Order By: Relevance
“…Several other studies have reported obstacles for disease noti cation similar to our ndings such as infrastructure issues and lack of human resources (20-23), lack of time (20,21,24,25) and lack of reporting forms/registers (25,26). These barriers were noted in the noti cation of other diseases like tuberculosis, malaria, and in uenza as well (21,(27)(28)(29).…”
Section: Discussionsupporting
confidence: 84%
“…Several other studies have reported obstacles for disease noti cation similar to our ndings such as infrastructure issues and lack of human resources (20-23), lack of time (20,21,24,25) and lack of reporting forms/registers (25,26). These barriers were noted in the noti cation of other diseases like tuberculosis, malaria, and in uenza as well (21,(27)(28)(29).…”
Section: Discussionsupporting
confidence: 84%
“…In Beitbridge district, Juru et al (2015) also found out that not knowing the right form to use can have a resultant negative bearing on ability to notify diseases of public health importance [6]. In Nigeria a study done by Lafond et al (2014) on reporting of notifiable diseases, showed that low knowledge on to whom they would report first affected effectiveness on identification and reporting of notifiable diseases thereby failing to notify notifiable diseases timeously [7].…”
Section: Discussionmentioning
confidence: 99%
“…Low performance could be due to lack of reporting guidelines. In Nigeria a study by Lafond et al (2014), suggested that in order to effectively identify and report notifiable diseases, reporting system requirements need to be clearly communicated to the participating health personnel and this improves the notification of the notifiable diseases [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of mobile phones proved not to be much reliable because only one health facility had electricity provided by means of a diesel-powered generator, hence posing challenges of running equipment such as computers, printers and charging mobile phones. The findings showed a worse effectiveness IDSR performance over the 2012 IDSR assessment in Nigeria, where 29% of Health facilities had computers and were powered by electricity through the use of generators and solar energy [17].…”
Section: Observational Check List Of Health Facilities In Rufunsa Dismentioning
confidence: 99%